Experimental characterisation of dry-joint masonry structures: Interface stiffness and interface damping - Vlachakis, Giorgios (2023)
The accurate description of the dynamics of dry-joint masonry structures strongly relies on the characterisation of the interaction at the units’ interfaces. Several experimental techniques are available for estimating the mechanical properties of the interface (i.e. stiffness and damping), yet, their reliability remains questionable given the lack of comprehensive comparative studies. This work presents an extensive experimental campaign on the meso-scale mechanics of dry-joint interfaces and quantifies both the interface stiffness and interface damping. Importantly, this paper reveals, for the first time, remarkable agreement of the interface stiffness estimated by inherently different experimental methods, namely deformation-based and vibration-based. Thus, it paves the way for the formulation of reliable constitutive laws that govern structural response in numerical modelling of dry-joint masonry structures.